A journey of living well: a participatory photovoice study exploring recovery and everyday activities with people experiencing mental illness. (4th March 2022) - Doroud, Nastaran; Fossey, Ellie; Fortune, Tracy; Brophy, Lisa; Mountford, Louise
Abstract: Background and Aim: Engagement in everyday activities has been identified as an important element in personal recovery from the experience of mental illness and a key priority for service-users. This study explored the role of everyday activities in recovery. Method: This study used a photovoice participatory research. Twenty-one participants experiencing mental illness were recruited from a community-managed mental health service in Melbourne, Australia. Data collection included individual interviews and photovoice courses. The courses included group discussions and required participants to take photographs about their everyday activities that support recovery. A lived experience co-facilitator contributed to development and delivery of the course. The interviews and group discussions were transcribed verbatim and analysed using constant comparative methods. Results: Recovery as a "journey of living well" was identified as the central theme that encompasses three interlinked categories: (1) living a life on hold; (2) choosing to recover; and (3) learning and navigating strategies. Conclusions: The findings suggest that recovery involves a range of experiences embedded in people's everyday lives. Recovery-oriented practice should provide opportunities for engagement in meaningful activities, to help consumers identify their potential and strategies to live well, and to adopt co-production at all levels.